Strategies to Locate Lost Persons with Dementia: A Case Study of Ontario First Responders - N. A. Neubauer; A. Miguel-Cruz; L. Liu (Journal of Aging Research)
Information on strategies and practices in the search of missing persons with dementia is inconsistent which creates challenges for first responders, such as police, when they choose appropriate search and rescue approaches. The purpose of this study was to describe current strategies among police services in Ontario. Telephone interviews with police were conducted. Questions included what strategies were used for locating missing persons living with dementia, and what gaps exist in search practices. Participants described they used high- and low-tech solutions in search and rescue. They identified gaps in education and awareness, proactive strategies, resources, and funding. Information collected from the interviews was used to develop a practice guideline for police in partnership with the Alzheimer Society of Ontario.